Testing Kuznets’ Hypothesis for Russian Regions: Trends and Interpretations - Alm, James R.; Grigoryev, Ruslan Arkadievich; Kramin, Marat Vladimirovich; Kramin, Timur Vladimirovich (Economy of Regions, 2016)
The paper established a number of "stylized facts", one of which is a confirmation of the S. Kuznets’ hypothesis of the nonlinear dependence between the degree of inequality in income distribution and welfare economic systems on the example of a group of Russian regions for the period 2002-2012. It is shown that, for a given sample, the welfare and economic growth factors amplify their influence on inequality in income distribution in the post-crisis period. The monotonous growth of income inequality which was observed before the crisis of 2008 is slowing in the process of raising the per capita gross regional product (GRP) during the post-crisis period, and for the foreseeable future, in some regions, its direction can be reversed, while maintaining a trend of socio-economic development. Despite the persistence over time of a convex nature of S. Kuznets’ curve for Russian regional data, its parameters changed during the reporting 2002-2012 period. The maximum point of the curve shifts to the left, its convexity increases. These facts indicate that the income inequality growth of the Russian regions’ as a result of growth of per capita GRP is slowing. For some regions in the post-crisis period, the income inequality does not grow with the growth of per capita GRP, or it even reduces. This fact can be attributed to the implementation of the Russian federal socially oriented projects and programs in recent years. The results can be used for the development of regional economic policy in order to regulate the level of income distribution inequality in the regions of Russia.